Framework-Driven Guideline Generation For AI Adoption: A Risk-Based Perspective - David Lau Keat Jin; Ganthan Narayana Samy; Fiza Abdul Rahim; Mahiswaran Selvananthan; Nurazean Maarop; Mugilraj Radha Krishnan; Sundresan Perumal (Journal of Theoretical and Applied Information Technology, 2026)
Indexed by Scopus/ERA